Hemangioma Pedis and Tuberculoma Pedis Sinistra in Children - Ferdiansyah MD; Mouly Edward; Muhammad Hardian Basuki; Ahmad Hannan Amrullah (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2018)
HISTORY: The girl 15 years old, had main complaint, there was a mass in her pedis since she got 2 years old, look red, no pain although in walk, size equal with the skin. The mass got bigger and pain in walk. The mass get bleedy after had crushed by stone, after that bleedy always happen when there was a contact, although soft touch. Patient had history contact with tuberculosis patient.INTERESTING POINTS FOR DISCUSSION: Tuberculoma is a mass that happened because infected bacil mycobacterium tuberculosis, hemangioma is a soft tissue mass that formed by vascular. hemangioma commonly happened in children about 4-10% in children’s tumor. It happened in a girl 3-5 more times than in a boy. Both of them are rare happen in the same time, especially in pedis. From this case, we  can found both type in the same patient.SOLUTION AND RATIONALE: For this case of soft tissue tumor,we use open biopsy. After we found the result , the best treatment for hemangioma and tuberculoma of the pedis for this case is below knee amputation.FINAL OUTCOME: For this case, the best treatment is amputation, and after amputation, the patient never complain about pain anymore, she feel satisfied and overall her quality of life is improving.